ChemInform Abstract: Total Synthesis and Complete Structural Assignment of Gambieric Acid A, a Large Polycyclic Ether Marine Natural Product. Issue 48 (2nd December 2014) - Sasaki, Makoto; Fuwa, Haruhiko
Abstract Review: [64 refs.